FIELD ASSESSMENT OF ACCESSIONS FROM THE MAIZE COLLECTION FOR RESISTANCE TO BOIL SMUT - V. N. Boyko (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. The efficiency of heterotic breeding is determined by reasonable selection of the lines with the best combining abilities and important breeding traits. It is possible to use the variability potential of the majority of traits when the level of resistance to the main diseases and pests is quite high. The most harmful disease of maize is common or boil smut (caused by Ustilago zeae (Beckm.) Unger). The breeding of resistant lines and hybrids of maize is the most rational, cheap and ecologically safe way to fight the disease. The initial stage of breeding work is the identification of pathogen-resistant forms.Materials and methods. In 2017, 594 accessions of six main Zea mays L. subspecies were studied using a score scale against the natural infectious background at the Kuban Experiment Station of VIR. The weather conditions (downpours and abrupt daily temperature fluctuations) were favorable for severe infection of maize plants with the pathogen.Results and conclusion. No disease symptoms were found in 173 accessions; 162 genotypes were affected only slightly. The greatest number of accessions with resistance to boil smut belonged to subsp. indentata (Sturt.) Zhuk. (69.4% of the total studied accessions), subsp. everta (69.2%) and subsp. semidentata (Sturt.) Zhuk. (66.7%). Accessions of subsp. amylacea (Sturt.) Zhuk. were more susceptible to the pathogen than other maize subspecies. The Russian, European and North American local maize varieties and self-pollinated lines had a low infection rate, while the accessions that came to the VIR collection from Asia and South America showed higher rates. After two years of comprehensive studies, the selected forms can be recommended for the use in breeding for immunity.